Binge eating in obesity: a longitudinal study following biliopancreatic diversion - Adami, G.F. (University of Genoa, Italy.); Gandolfo, P; Meneghelli, A; Scopinaro, N (The International journal of eating disorders, 1996)
Objective: Evaluating the influence of dieting and of being overweight on binge-eating episodes and on psychological traits in severely obese patients. Method: Clinical interviews and self-report questionnaires prior to and 2 years following biliopancreatic diversion (BPD) when subjects adopt a completely free eating style and achieve in maintaining a normal or nearly normal body weight. Results: At two years following the operation, the prevalence of binge-eating episodes sharply fell and the subjects' overall psychological conditions improved; only a few patients started binging. Discussion: These results point out the importance of dieting and of overweight itself in determining eating behavior disturbances or psychopathology. The fact that only a very small number of patients continue or start binging following BDP suggests that a minority of obese bingers should be considered as true eating-disordered patients